2007
DOI: 10.2337/db07-0767
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte Death, Adipose Tissue Remodeling, and Obesity Complications

Abstract: OBJECTIVE-We sought to determine the role of adipocyte death in obesity-induced adipose tissue (AT) inflammation and obesity complications.RESEARCH DESIGN AND METHODS-Male C57BL/6 mice were fed a high-fat diet for 20 weeks to induce obesity. Every 4 weeks, insulin resistance was assessed by intraperitoneal insulin tolerance tests, and epididymal (eAT) and inguinal subcutaneous AT (iAT) and livers were harvested for histological, immunohistochemical, and gene expression analyses.RESULTS-Frequency of adipocyte d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

71
828
8
11

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 856 publications
(918 citation statements)
references
References 52 publications
71
828
8
11
Order By: Relevance
“…As expected from previous studies, the group initially observed that following 16 weeks of HFD feeding, a high degree (approximately 80%) of adipocyte cell death was evident in epididymal AT (13). However, a fascinating twist to these findings was that at the 20-week stage, the percentage of necrotic cells was reduced to approximately 16%; this was accompanied by an increased emergence of smaller adipocytes (<5,000 μm 2 ), thus restoring the adipocyte number (13). These key findings lend support to a model in which the progression of obesity is associated with AT remodeling, expanding largely through hypertrophy, subsequently requiring adipocytes to undergo an initial "necrotic wave," with later stages relying on hyperplastic expansion.…”
Section: Figuresupporting
confidence: 57%
See 2 more Smart Citations
“…As expected from previous studies, the group initially observed that following 16 weeks of HFD feeding, a high degree (approximately 80%) of adipocyte cell death was evident in epididymal AT (13). However, a fascinating twist to these findings was that at the 20-week stage, the percentage of necrotic cells was reduced to approximately 16%; this was accompanied by an increased emergence of smaller adipocytes (<5,000 μm 2 ), thus restoring the adipocyte number (13). These key findings lend support to a model in which the progression of obesity is associated with AT remodeling, expanding largely through hypertrophy, subsequently requiring adipocytes to undergo an initial "necrotic wave," with later stages relying on hyperplastic expansion.…”
Section: Figuresupporting
confidence: 57%
“…Strissel and colleagues provided key answers to this question by assessing the progression of adipocytes and macrophages in AT of HFD-fed mice. As expected from previous studies, the group initially observed that following 16 weeks of HFD feeding, a high degree (approximately 80%) of adipocyte cell death was evident in epididymal AT (13). However, a fascinating twist to these findings was that at the 20-week stage, the percentage of necrotic cells was reduced to approximately 16%; this was accompanied by an increased emergence of smaller adipocytes (<5,000 μm 2 ), thus restoring the adipocyte number (13).…”
Section: Figurementioning
confidence: 51%
See 1 more Smart Citation
“…In this regard, Khan et al reported that mice lacking collagen VI, which is expressed abundantly in adipose tissue, exhibit the uninhibited adipose tissue expansion and substantial improvements in insulin sensitivity on a high-fat diet [67]. These findings suggest that reduced lipid storage in obese adipose tissue may contribute to ectopic lipid accumulation in non-adipose tissues such as the liver, skeletal muscle, and pancreas, where lipotoxicity impairs their metabolic functions [10,[71][72][73]. Although the molecular mechanisms underlying adipose tissue fibrosis are still largely unknown, recent evidence suggests that a PPARγ-fibroblast growth factor 1 (FGF1) axis is required for obesity-induced adipose tissue remodeling [74].…”
Section: Novel Regulators Of Adipose Tissue Inflammationmentioning
confidence: 97%
“…This is more pronounced in visceral, hepatic and epicardial than in subcutaneous fat [54]. Concomitantly, there is death of single adipocytes and secretion of pro-inflammatory cytokines, chemokines and other adipokines from immune cells and/or adipocytes [55] that contributes to further recruitment of macrophages and adipositis. Other associated changes are ectopic fat deposition in several organs, including beta cells, endoplasmic reticulum stress, compromised fatty acid oxidation, increased levels of circulating non-esterified fatty acids and other lipids [24] and as observed in mice, dysfunction of neural regulatory systems such as leptin resistance, again closely linked with local inflammation [56].…”
Section: Excess Nutrients/obesitymentioning
confidence: 99%